(untitled) (Research, Society and Development, 2021)
Objective: To identify, in the literature, factors related to the role of the nurse, within the context of mental care, focusing on an autistic client, in relation to the importance of the family bond. Methodology: This is an integrative literature review, based on articles available in the Virtual Health Library – VHL. Results and Discussion: Of the 75 articles found, after the inclusion and exclusion criteria, 10 national scientific articles were examined and discussed, with the theme “Social and family aspects of children with Autistic Spectrum Disorder; Importance of early diagnosis; Nurse’s Role in Customer Care with Autistic Spectrum Disorder.”. Conclusion: Autism is an unknown topic for the lay population and this lack of knowledge has been hindering the insertion of these children in the social and family context. This compromises the child’s cognitive and affective development. Therefore, the role of nurses within the assistance to autistic clients and their families through the Systematization of Nursing Care (SAE) is of great importance.